Perkembangan Teknologi Media Pembelajaran Bahasa Arab - Fazri Nur Insan; Acep Hermawan (Al-Fakkaar, 2023)
Technology has revolutionized the way we learn in education, and this paper explores its roles and significance in understanding the Arabic language. In this paper, we will delve into the concept of instructional media technology, how it operates, and why it is highly relevant in the context of acquiring the Arabic language. Instructional technology employs digital tools to enrich the learning experience, encourage engagement, and create various avenues for active involvement in learning materials. In the realm of the Arabic language, technology plays a pivotal role. The intricate and distinct nature of the Arabic language demands a precise approach for profound comprehension. Technology aids in accurate pronunciation practice and facilitates adaptation to various learning styles. Arabic language educators acknowledge the necessity of blending tradition with technology, crafting a more comprehensive and effective learning environment. With resources like interactive platforms, specialized language applications, and audiovisual content, Arabic language learners can authentically engage with the language, strengthen linguistic connections, and transform language acquisition in the technology-driven educational landscape. Technology enables us to achieve a deeper and more comprehensive understanding of the Arabic language, ushering in new opportunities in the ever-evolving realm of learning.